2022
DOI: 10.1021/acsapm.1c01768
|View full text |Cite
|
Sign up to set email alerts
|

Fast, Localized, and Low-Energy Consumption Self-Healing of Automotive Clearcoats Using a Photothermal Effect Triggered by NIR Radiation

Abstract: Dynamic polymer networks containing photothermal materials have been reported to demonstrate highly efficient intrinsic self-healing under irradiation. In particular, organic near-infrared-absorbing ionic salts, such as diimmonium dyes, function as transparent polymer heaters and can enhance the self-healing properties of clearcoats. In this study, we designed a self-healing automotive clearcoat with a reversible polymer network based on acryl polyol (AP) and dynamic hindered urea (HU) bonds and introduced N-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…56 More recently, our group introduced a self-healing automotive clearcoat containing an organic photothermal dye and showed that the clearcoat can be activated by sunlight. 46 Among these systems, photothermal self-healing is advantageous over other mechanisms in that it provides a fast and highly efficient self-healing process of the hard coating (>10 3 MPa in indentation hardness and modulus) by elevating the surface temperature of the coating in response to a specific adsorption band in sunlight. However, there is a limitation in controlling the optical properties of aliphatic self-healing poly(urethane acrylate)s because their refractive indexes inherently converge at ∼1.5.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…56 More recently, our group introduced a self-healing automotive clearcoat containing an organic photothermal dye and showed that the clearcoat can be activated by sunlight. 46 Among these systems, photothermal self-healing is advantageous over other mechanisms in that it provides a fast and highly efficient self-healing process of the hard coating (>10 3 MPa in indentation hardness and modulus) by elevating the surface temperature of the coating in response to a specific adsorption band in sunlight. However, there is a limitation in controlling the optical properties of aliphatic self-healing poly(urethane acrylate)s because their refractive indexes inherently converge at ∼1.5.…”
Section: Introductionmentioning
confidence: 99%
“…When a self-healable optical protective coating is applied directly to an optical lens surface with various ranges of refractive power, it is highly desirable for the refractive index conditions of the self-healable coating material to be controllable over a wide range to avoid generating stray light between adjacent optical layers. In most outdoor applications, autonomous self-healing capability under ambient sunlight conditions is better for energy efficiency and user convenience and safety . The self-healing function needs to be achievable for deeply scratched surfaces or those with random multiple surface damages.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The motivation for self-healing materials comes from the self-repair characteristic of natural materials, such as healing of damaged skins of trees and animals. Various self-healing polymers (SHPs) have been developed, shifting engineering problems from maintenance related to recycling, thereby lowering the overall costs of processing and mechanical failure in different industrial processes. SHPs are smart materials that can heal and restore their properties when aided by the required external stimulus such as radiations, temperature, pH, and magnetic field. , In the most recent years, ultrafast recovery systems have been made from these SHPs which have been successfully utilized as wearable electronics, cut-detecting sensors, automotive coatings, and many more. …”
Section: Introductionmentioning
confidence: 99%